MULTIMODAL BOOKS AS A BRIDGE FOR THE NET GENERATIONS - Theresia Enny Anggraini (Prosiding Seminar Nasional Bahasa, Sastra, dan Seni (Sesanti), 2019)
For those who were born in the seventies and after, electronic gadgets might have become their first playing tools. These generations had been so used to using these electronic gadgets that a lot of them forgot or did not know how to use manual tools and equipment. There was a story about a young boy who was given a book for the first time, while usually reading on a tablet. He was trying to swipe the page instead of turning it over. For these generations, reading a traditional book might not be their first choice since they spend a lot of time on their gadgets. However, reading is still a very important habit that needs to be taught to the young. To get their interests to read a book, a bridge needs to be made so that a smooth transition from reading in a gadget to reading a book can be achieved. In this presentation, I would like to discuss some multimodal books that consist of not only texts but also other types of mode representing internet or cellphone page. In books like ttyl, ttfn, i-Drakula, and An Order of Amelie, Hold the Fries, the authors are using IM (Instant messaging), text messages, emails, web browsers, and even memos. Thus, the net generation will read books that will feel like a gadget page as a bridge to read regular books and textbooks later on.